Assessing Police Attitudes Toward Drugs and Drug Enforcement - Petrocelli, Matthew (American journal of criminal justice, 2014)
The American War on Drugs has been a long and protracted battle. On the front lines are local, state and federal drug enforcement officers who are tasked with pursuing drug users and dealers. Empirically, officers’ attitudes about the laws they uphold have been shown to impact how aggressively they enforce those laws and the discretion they employ. Although there is a well established body of literature which documents the importance of discretionary dynamics in many areas of law enforcement, we know almost nothing about narcotics officers’ attitudes toward drugs and drug enforcement. Hence, we are unaware of extremely important variables that almost certainly impact and influence front line drug officers. This study fills that gap by examining the survey responses of over 1,000 drug interdiction officers at all levels of law enforcement, measuring their attitudes toward various drugs and the relative harm they incur, along with existing and proposed policies and strategies. The results are discussed in terms of their enforcement and policy implications.